The Kraft Heinz Company global nutrition targets for the innovation and reformulation of food and beverages: Current and future directions - Yu, Lynn; Braesco, Véronique; Cooper, Sheri L.; Drewnowski, Adam; Esteves, Bridget Hannon; Budelli, Andrea Luigi (Frontiers in Nutrition, 2023)
Reformulating packaged foods has the potential to improve the nutrient density of the global diet. The present perspective illustrates The Kraft Heinz Company’s approach to product (re) formulation to develop healthier product lines that are lower in saturated fats, total sugars, and sodium, and contain health promoting components. Here we present the rationale for The Kraft Heinz Company’s global nutrition targets used for the global innovation and renovation of foods and beverages. The global nutrition targets use a category specific approach to set maximum levels for the main nutrients of public health concern: saturated fat, total sugars and sodium, taking into account product’s characteristics (typical portion size, eating occasion, role in the diet, etc.) as well as regulatory, technological, sensory and safety constraints. Benchmarking examples illustrate how the nutrition targets are positioned within the U.S., France and Australia. These global nutrition targets serve as part of The Kraft Heinz Company’s environmental, social and governance nutrition commitments and demonstrates how the food industry is improving the nutritional value of packaged foods and beverages both now and into the future.